Glo-ubuntu as an extension of Global Citizenship Education: Cultivating the notion of an African university - Terblanche, J.; Waghid, Y. (South African Journal of Higher Education, 2023)
In previous work (Waghid et al. 2023) we offered an account of ubuntu and its implications for South African higher education. The main thrust of our argument is constituted by understanding that ubuntu involves interdependent-cum-autonomous human relations that impact university education in expansive ways: independent and collaborative with the possibility of being forward-looking. Yet, what we have not done hitherto, is to examine ubuntu in the realm of global citizenship education, considering the latter seems to intertwine with constitutive aspects of ubuntu. In this article, we reconsider ubuntu with global citizenship education (GCE) and its implications for higher education. Firstly, we proffer an understanding of GCE about pedagogical praxis; secondly, we show how ubuntu can advance GCE within higher education; and thirdly, we examine some of the implications of a glo-ubuntu for higher education in South Africa.